Discovery and Characterization of a Cryptic Secondary Binding Site in the Molecular Chaperone HSP70 - O’connor, Suzanne; Le Bihan, Yann-Vaï; Westwood, Isaac M.; Liu, Manjuan; Mak, Oi Wei; Zazeri, Gabriel [UNESP]; Povinelli, Ana P. R. [UNESP]; Jones, Alan M.; van Montfort, Rob; Reynisson, Jóhannes; Collins, Ian (MDPI, 2022)
Heat Shock Protein 70s (HSP70s) are key molecular chaperones that are overexpressed in many cancers and often associated with metastasis and poor prognosis. It has proven difficult to develop ATP-competitive, drug-like small molecule inhibitors of HSP70s due to the flexible and hydrophilic nature of the HSP70 ATP-binding site and its high affinity for endogenous nucleotides. The aim of this study was to explore the potential for the inhibition of HSP70 through alternative binding sites using fragment-based approaches. A surface plasmon resonance (SPR) fragment screen designed to detect secondary binding sites in HSP70 led to the identification by X-ray crystallography of a cryptic binding site in the nucleotide-binding domain (NBD) of HSP70 adjacent to the ATP-binding site. Fragment binding was confirmed and characterized as ATP-competitive using SPR and ligand-observed NMR methods. Molecular dynamics simulations were applied to understand the interactions with the protein upon ligand binding, and local secondary structure changes consistent with interconversion between the observed crystal structures with and without the cryptic pocket were detected. A virtual high-throughput screen (vHTS) against the cryptic pocket was conducted, and five compounds with diverse chemical scaffolds were confirmed to bind to HSP70 with micromo-lar affinity by SPR. These results identified and characterized a new targetable site on HSP70. While targeting HSP70 remains challenging, the new site may provide opportunities to develop allosteric ATP-competitive inhibitors with differentiated physicochemical properties from current series.
Keywords: Cryptic pocket; Fragment screen; HSP70; Molecular dynamics; Virtual screen